Case report: Diagnostic trap: a extremely rare metastatic myoepithelial carcinoma of breast - Luo, Shuai; Tian, Xiaoxue; Xu, Ting (Frontiers in Oncology, 2024)
BackgroundMyoepithelial carcinoma (MECA) is a malignant tumor primarily affecting the salivary gland, most frequently in the parotid gland. It can manifest as primary or secondary to pleomorphic adenoma or benign myoepithelioma. MECA exhibits aggressive behaviors. In particular, primary MECA is more aggressive, frequently recurring or metastasizing distantly. Its morphological and immunohistochemical characteristics overlap with various tumors, posing challenges in its recognization as a distinct entity. Consequently, MECA may be frequently misdiagnosed, mainly when occurred in the mammary gland. This chance for misdiagnosis poses significant challenges in clinical diagnosis and treatment.Case demonstrationA 77-year-old woman with a history of pleomorphic adenoma presented with a palpable lump in the right breast for 3 months. Subsequent core needle biopsy (CNB) and modified radical mastectomy were performed, with samples subjected to histopathological examination. Based on the patient’s history, histomorphologic features, immunohistochemistry (IHC) results and results of FISH, the pathological diagnosis confirmed MECA in the mammary gland. Postoperative chemotherapy was administered, and the patient exhibited a favorable prognosis during a 40-month follow-up period.ConclusionsPrimary MECA in the mammary gland is exceedingly rare, metastasis from the salivary gland MECA to the mammary gland is even rarer and has not been previously reported. This study presents the first documented case of MECA originating from the parotid gland metastasizing to the mammary gland (also known as breast). Highlighting this case aims to raise awareness among clinical pathologists to prevent underdiagnosis and misdiagnosis of this tumor entity.